The determinants of the bank regulation and supervision on the efficiency of Islamic Banks in different country’s income level - Mohd Noor, Nor Halida Haziaton; Bakri, Mohammed Hariri; Wan Yusof, Wan Yusrol Rizal; Mohd Noor, Nor Raihana Asmar; Abdullah, Hasni; Mohamed, Zulkifli (Korea Distribution Science Association (KODISA), 2020)
This study investigates the impact of the country's governance on the revenue efficiency of 108 Islamic banks from 26 countries offering‎ Islamic banking and finance products services. The technical efficiencies of individual Islamic banks have been analyzed using the Data ‎Envelopment Analysis method. The data will be pooled across the selected countries and utilize the intermediation approach. The Ordinary‎ Least Square estimation method is employed to examine the impact of country supervision and regulation on the technical efficiency of ‎Islamic banks. As robustness check, the study examines the impact of the level of bank regulations and supervision on the efficiency of ‎Islamic banks operating in different income-level countries. The results found that the stricter the supervisory power, the less strict capital ‎requirement, the tighter the restrictions on non-banking activities, and the stricter the private monitoring enhance statistically significantly ‎the level of efficiency of Islamic banks. In upgrading the regulations and supervision of the Islamic banks, the existing regulatory framework ‎based on the Basel Committee on Banking Supervision (BCBS) must be complemented with the prescriptions on Islamic banking or Shariah ‎compliance diligently, so that the Islamic banks could be regulated accurately and further improve the technical efficiency of their operations.